BIOACTIVE COMPOUNDS FROM RHIZOPHORA APICULATA AND THEIR ANTI-DIABETIC AND ANTI-COAGULANT PROPERTIES - Hansika Sunil Kumar, Dr. Abirami Arthanari, Dr.Sivaperumal.P (Chelonian Research Foundation, 2023)
Introduction: This study explores the therapeutic potential of Rhizophora apiculata, a mangrove species, focusing on its anti-diabetic and anti-coagulant effects. With diabetes and coagulation disorders being significant health concerns, this research investigates the plant's bioactive compounds. While earlier studies hinted at these properties, comprehensive investigations are needed to understand mechanisms, efficacy, and safety. Materials and Methods: The study collected Rhizophora apiculata samples, prepared solvent extracts, and conducted anti-diabetic and anticoagulant assays. Results demonstrated concentration-dependent inhibition percentages, aligning with variations in similar plant extracts. Rhizophora apiculata showed promise as an anti-diabetic agent, but further clinical studies are needed to confirm practical use. Results : This study presents alpha-amylase and alpha-glucosidase inhibition results. Alpha-amylase inhibition percentages ranged from 9% to 47%, peaking at 75% concentration. Alpha-glucosidase inhibition ranged from 19% to 54.3%, with the highest at 100% concentration. Variable inhibition indicates potential bioactivity in these samples. Discussion: The study discusses the concentration-dependent nature of inhibition percentages and# the need to consider extraction methods and assay conditions. It notes Rhizophora apiculata's potential as an anti-diabetic agent, but emphasises the importance of clinical studies and considering inhibition specificity and diabetes variations. Conclusion: Rhizophora apiculata holds promise as a source of natural compounds with anti-diabetic and anti-coagulant potential. Further research, including clinical trials, is required to fully understand its therapeutic potential. This study offers insights into developing novel treatments for diabetes and coagulation disorders. Keywords :Rhizophora apiculata,Anti-diabetic,Anti-coagulant,Bioactive compounds,Inhibition percentages,Clinical studies